The introduction of the gold standard in Portugal - Mendonça, António (2022)
The first half of the XIX century is a period of deep political, economical and social transformations in Portugal. The crisis of the Ancient Society extended itself with the French invasions, the civil war between the liberal arid absolutist forces and the feebleness of the new governments, until the 1850's. The second half of the XIX century is the period of the consolidation of the new politica and economical structures which meant to Portugal the late entrance in the world of the capitalist market relations. The Gold Standard was introduced in the country in 1854 and lasted until 1891. It was the expression of the new order but also an instrument of the british domination in Portugal. This monetary regime coincids with a period of a certain growth and stability of prices.